Nuclear resonance vibrational spectroscopy (NRVS) of rubredoxin and MoFe protein crystals - Guo, Yisong (Hyperfine Interact, 2012)
We have applied (57)Fe nuclear resonance vibrational spectroscopy (NRVS) for the first time to study the dynamics of Fe centers in Fe-S protein crystals, including oxidized wild type rubredoxin crystals from Pyrococcus furiosus, and the MoFe protein of nitrogenase from Azotobacter vinelandii. Thanks to the NRVS selection rule, selectively probed vibrational modes have been observed in both oriented rubredoxin and MoFe protein crystals. The NRVS work was complemented by extended X-ray absorption fine structure spectroscopy (EXAFS) measurements on oxidized wild type rubredoxin crystals from Pyrococcus furiosus. The EXAFS spectra revealed the Fe-S bond length difference in oxidized Pf Rd protein, which is qualitatively consistent with the X-ray crystal structure.